Functional characterization of USP39 as a caretaker in maintaining genomic stability - 황이슬 (The Graduate School, Ajou University, 2024)
Mutual crosstalk among poly(ADP-ribose) (PAR), activated PAR polymerase 1 (PARP1) metabolites, and DNA repair machinery has emerged as a key regulatory mechanism of the DNA damage response (DDR). However, there is no conclusive evidence of how PAR precisely controls DDR. Herein, six deubiquitinating enzymes (DUBs) associated with PAR-coupled DDR were identified, and the role of USP39, an inactive DUB involved in spliceosome assembly, was characterized. USP39 rapidly localizes to DNA lesions in a PAR-dependent manner, where it regulates non- homologous end-joining (NHEJ) via a tripartite RG motif located in the N-terminus comprising 46 amino acids (N46). Furthermore, USP39 acts as a molecular trigger for liquid demixing in a PAR-coupled N46-dependent manner, thereby directly interacting with the XRCC4/LIG4 complex during NHEJ. In parallel, the USP39-associated spliceosome complex controls homologous recombination repair in a PAR-independent manner. In addition, accumulated evidence showed post-translational modifications (PTMs) of histones are crucial for a wide range of biological processes such as replication, transcription, and the DDR. In particular, dynamic changes in histone modifications are critical for regulating double-strand break (DSB) repair in the DDR. PARP1 plays a key role as a major histone modifier that modulates chromatin structure for precise DNA repair. However, the process through which PARP1 controls the chromatin structure through histone modifications in DNA lesions remains unclear. In the present study, I identified Suppressor of variegation 3-9 homolog 1 (SUV39H1) as a direct PAR-mediated USP39 binding protein that catalyzes histone 3 lysine 9 trimethylation (H3K9me3) for heterochromatin formation. USP39 colocalizes with SUV39H1, and depletion of USP39 reduces SUV39H1 and H3K9me3 levels as well as heterochromatin formation, suggesting that USP39 participates in the maintenance of chromatin structure through SUV39H1-mediated H3K9me3. Our results also show that USP39 stimulates chromatin organization and activation of ataxia-telangiectasia mutated (ATM) around DNA break sites to facilitate DNA repair. These findings provide mechanistic insights into the process by which PAR chains precisely control DNA repair and chromatin dynamics in the DNA damage response, and indicate the functional role of USP39 in regulating the DDR to maintain genomic stability.
학위논문(박사)--의생명과학과,2024. 8
Keywords: Ataxia telangiectasia mutated kinase; Chromatin dynamics; DNA damage response; Deubiquitinating enzymes; Histone methyltransferase; Liquid demixing; Poly (ADP-ribose) polymerase 1